An optimality criterion for the crossing number - Székely, László (Ars mathematica contemporanea, 2008)
A suffcient condition is given that a certain drawing minimizes the crossing number. The condition is in terms of intersections in an arbitrary set system related to the drawing, and is like a correlation inequality.
Keywords: matematika; prekrižno število; risanje grafov; teorija grafov